Improving Elementary School Students' Mathematics Problem Solving Skills through Problem-Based Learning (PBL) Based on Higher Order Thinking Skills (HOTS) - Munawaroh, Qomsiatun; Dewi Wulandari, Murfiah; Tina Maya Astuti, Heni (UIN Raden Mas Said Surakarta, 2024)
Mathematics is a subject that requires critical and creative thinking skills to solve problems. Meanwhile, this research aims to determine the effectiveness of using problem-based learning (PBL) based on higher-order thinking skills (HOTS) to improve students' mathematical problem-solving skills. This research is classroom action research with two cycles, each consisting of planning, implementation, observation (act & observe), and reflection. This research targeted 11 fifth-grade students at SDN Wirogunan 03. Data was obtained from the results of formative tests by answering ten questions and observation sheets of learning activities. The research results showed that students' mathematical problem-solving skills had increased. Cycle I experienced an average increase of 17.95%, and cycle II experienced an average increase of 31.85%. The research results show that HOTS-based PBL can improve students' mathematical problem-solving skills and effectively improve the mathematics learning outcomes of fifth-grade students at SDN Wirogunan 03 Kartasura